Analysis of direct‐acting antiviral‐resistant hepatitis C virus haplotype diversity by single‐molecule and long‐read sequencing. Issue 7 (31st March 2022) - Yamauchi, Kozue; Sato, Mitsuaki; Osawa, Leona; Matsuda, Shuya; Komiyama, Yasuyuki; Nakakuki, Natsuko; Takada, Hitomi; Katoh, Ryo; Muraoka, Masaru; Suzuki, Yuichiro; Tatsumi, Akihisa; Miura, Mika; et al.
Abstract: The method of analyzing individual resistant hepatitis C virus (HCV) by a combination of haplotyping and resistance‐associated substitution (RAS) has not been fully elucidated because conventional sequencing has only yielded short and fragmented viral genomes. We performed haplotype analysis of HCV mutations in 12 asunaprevir/daclatasvir treatment‐failure cases using the Oxford Nanopore sequencer. This enabled single‐molecule long‐read sequencing using rolling circle amplification (RCA) for correction of the sequencing error. RCA of the circularized reverse‐transcription polymerase chain reaction products successfully produced DNA longer than 30 kilobase pairs (kb) containing multiple tandem repeats of a target 3 kb HCV genome. The long‐read sequencing of these RCA products could determine the original sequence of the target single molecule as the consensus nucleotide sequence of the tandem repeats and revealed the presence of multiple viral haplotypes with the combination of various mutations in each host. In addition to already known signature RASs, such as NS3‐D168 and NS5A‐L31/Y93, there were various RASs specific to a different haplotype after treatment failure. The distribution of viral haplotype changed over time; some haplotypes disappeared without acquiring resistant mutations, and other haplotypes, which were not observed before treatment, appeared after treatment. Conclusion : The combination of various mutations other than the known signature RAS was suggested to influence the kinetics of individual HCV quasispecies in the direct‐acting antiviral treatment. HCV haplotype dynamic analysis will provide novel information on the role of HCV diversity within the host, which will be useful for elucidating the pathological mechanism of HCV‐related diseases. Abstract : We performed haplotype analysis of HCV mutations in direct‐acting antivirals (DAA) treatment failure cases using Oxford Nanopore sequencer enabling single‐molecule, long‐read sequencing using rolling circle amplification (RCA), and revealed the presence and the dynamics of multiple viral haplotypes with the combination of various mutations in each host. HCV haplotype dynamic analysis will provide novel information on the role of HCV diversities within the host, which is useful for elucidation of the pathological mechanism of HCV related diseases.image